Shallow anterior chamber depth: is this a contraindication, or are there options for phakic lens implantation? (Ukrainian Journal of Ophthalmology, 2025)
Background. High myopia is a refractive error and a serious problem among teenagers. This condition can lead to significant vision impairment if left unaddressed, affecting their daily activities and overall quality of life.Purpose. To estimate clinical results after phakic lens implantation in patients with high myopia and shallow anterior chamber depth during the 24-month postop period. Material and methods. In this retrospective observational study, we aimed to analyze clinical results of 226 eyes in 131 patients who had undergone implantable collamer lens (ICL) implantation. Pre- and postoperative clinical parameters have been evaluated at 1 day, 1 week, 1, 3, 6, 12 and 24 months in the postoperative period.Results. A total of 226 eyes of 131 patients had underwent ICL implantation in Republican Specialized Scientific and Practical Medical Center of Eye Microsurgery from January 2020 to December 2023. Initially, we separated all eyes into two groups. Group A that had anterior chamber depth (ACD) ≥ 2.8 mm and Group B that had an ACD < 2.8 mm. The mean pre-op ACD was 2.95±0.13 mm was 2.65±0.15 mm in Group A and B, respectively. The mean age of all patients was 25.68±4.3. The mean pre-op manifest spherical equivalent was -8.65±2.72 D, and the manifest cylinder was -2.43±0.53 D, respectively (p≤0.001), with postoperative refractive measures reduced to -0.5±0.12 D (p≤0.001). The mean IOP was 14.8±2.3 mmHg preoperatively. The mean IOP has changed to 15.23±1.86 mmHg during 24 months in the postoperative period. Conclusion. Phakic IOL implantation is an alternative method for correcting high refractive errors. Even when the anterior chamber depth is below the required parameters, the surgeon can still implant ICL and achieve optimal postoperative results. However, in these cases, all patients must be thoroughly prepared for the planned surgery and should be monitored periodically for intraocular pressure and ICL vault measurements during the long-term postoperative period.
Keywords: myopia; visual acuity; implantable collamer lens; phakic; corneal endothelium; intraocular pressure; anterior chamber